CRITICAL REVIEW OF DRAGOŠ KALAJIĆ’S “MAP OF (ANTI)UTOPIAS” - Gajić, Aleksandar (National interest, 2026)
The first, theoretically most lively and controversial work in Serbia on utopias, Map of (Anti)utopias, was published by Dragoš Kalajić in 1978. The Paper, in its first part, places Kalajić’s book within the corpus of works that study utopias and utopian thinking, defining their content and basic characteristics, to begin the analysis of Kalajić’s contribution to the study of this topic and the specificity of the angle from which he explained utopian ideas and processes. The second part of the Paper, using methods of content analysis and comparison, identifies models that served as starting points for Kalajić’s study of utopias among traditionalist thinkers, especially the teachings of Julius Evola, a right-wing traditionalist whose significant influence shaped Kalajić’s entire thought. The third, final part of the Paper provides a critical overview of the scope of Kalajić’s study and calls for, taking into consideration his significant contribution to the research on utopias, as well as some perceived shortcomings, a nuanced approach to the “mapping” of this topic.